Enabling an Accelerated Development Path for Chlorhexidine Digluconate Gel 7.1% w/w for the Prevention of Omphalitis - Elena De Angelis; L Immins; N Jibry; D Hunt; K Cheng; P Chowdhury; C Patel; S Wilhelm; P Williams (University of Huddersfield Press, 2018)
In 2012, the United Nations (UN), identified chlorhexidine as a Life-saving Commodity and called for the development of a chlorhexidine product suitable for the prevention of omphalitis (umbilical cord infection) in developing countries. In response, GlaxoSmithKline (GSK) set out to develop a chlorhexidine digluconate 7.1% w/w gel, in partnership with Save the Children. The vision was to develop a gel which could pass a stringent regulatory review thereby assuring a safe, effective, and quality product. Review under the European Medicines Agency's (EMA) Article 58 pathway was pursued, with accelerated assessment granted. The regulatory dossier compiled literature-based evidence for clinical efficacy and safety, supplemented by GSK-generated in-vitro studies and a full CMC data package to support the quality. No new clinical trial data or in vivo non-clinical study data were submitted. A positive opinion from the EMA was received in 2016. The time from the initial UN call to EMA Positive Opinion was 3 years and 7 months.